2015
DOI: 10.1074/jbc.m115.673467
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Affinity of Cel7A Carbohydrate-binding Module for Lignin

Abstract: Background: Non-productive adsorption to lignin hinders cellulase efficiency.Results: 31 alanine mutants of the carbohydrate-binding module (CBM) exhibit highly correlated cellulose and lignin affinity.Conclusion: The cellulose-binding face of CBM is responsible for the majority of lignin affinity, although four mutations were identified that selectivity decrease lignin adsorption.Significance: The mutations studied inform future engineering efforts of fungal CBMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 37 publications
3
62
0
Order By: Relevance
“…Mutations were made by site directed mutagenesis (Zheng et al, ). Expression and purification was performed as previously described (Strobel et al, ). Briefly, SC‐Trp medium was inoculated with S. cerevisiae containing the Cel7A gene and grown for 3 days at 30°C, 220 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations were made by site directed mutagenesis (Zheng et al, ). Expression and purification was performed as previously described (Strobel et al, ). Briefly, SC‐Trp medium was inoculated with S. cerevisiae containing the Cel7A gene and grown for 3 days at 30°C, 220 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…The T. reesei Cel7A linker and CBM were produced with a homologous Cel7A CD from Talaromyces emersonii (Te‐Tr chimera) to enable efficient expression in Saccharomyces cerevisiae . Four residues in the CBM (Q2, H4, V18, and P30) were chosen for mutation based on favorable changes in cellulose/lignin adsorption selectivity when previously mutated to alanine (Strobel et al, ). Three additional residues (Y5, V27, and L28) were selected for mutation due to their hydrophobic nature.…”
mentioning
confidence: 99%
“…Cellulases modified by succinylation to negatively charge the protein surface showed final higher conversion of Avicel in the presence of lignin compared with controls, suggesting that the electrostatic potential on a protein is also relevant for lignin‐mediated inactivation. Strobel et al investigated lignin adsorption behavior for a series of mutants of a family 1 CBM (Pfeiffer et al, ; Strobel et al, , ). Mutation of some residues lowered lignin adsorption without a corresponding loss of CBM1 binding to crystalline cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Strong bindings of Trichoderma reesei CBH-I and EG-I to both cellulose and lignin were observed using quartz crystal microgravimetry (Martín et al, 2013). Other studies reported that the cellulose binding domain of the effluent enzyme played a significant role in the unspecific binding of cellulases to lignin (Palonen et al, 2004;Rahikainen et al, 2013;Strobel et al, 2015Strobel et al, , 2016. T. longibrachiatum, which are taxonomically separable from T. reesei, could also act as a potential cellulase candidate with high activities (Kubicek et al, 1996).…”
mentioning
confidence: 98%